Pelatihan Manajemen Organisasi Untuk Meningkatkan Pengetahuan Founder Dan Pengurus Dalam Fungsi Organisasi Ikatan Motor Honda Di Jawa Barat - Gunardi Gunardi; Hendriady De Keizer; Siti Nur Khoiriyah Ramadani; Dila Maulida Khaerunnisa; Tatiek Ekawati Permana (Universitas Insan Cendekia Mandiri, 2024)
Non-profit organizations play a vital role in society, but often face challenges in managing resources and achieving goals. This organizational management training is specifically designed to enhance the competence of founders and administrators in effectively managing the West Java Honda Motorcycle Association (Ikatan Motor Honda Jawa Barat). The training covers important modules such as understanding the organization's vision, mission, and objectives, organizational governance, human resource management, financial management, project and program management, communication and public relations, as well as leadership and organizational development. This training is crucial for non-profit organizations like the Association to continue to grow and make a significant contribution in achieving the social objectives of the West Java Honda Motorcycle Association (Ikatan Motor Honda Jawa Barat).